Acessibilidade por diálogos de mediação: desenvolvimento e avaliação de um assistente de navegação para a web - Monteiro, Ingrid Teixeira (2011)
Web accessibility is one of the big challenges in the Computer Science research. There are many initiatives that aim to improve systems, in order that users with disabilities and other special needs have plain access to information and services available on the Internet. One of them is the system presented here, WNH, a Web Navigation Helper, created to support users with special needs do activities on the Internet, through mediation dialogs, previously developed, with a specialized editor, by users interested in helping these people. We present in the text, the description of the developed tools (the editor and the helper) and the analysis of three exploratory studies done, before and after the system development. We also show how the experiments revealed social and cultural aspects of Brazilian society, that are relevant to the WNH design, and we show how they changed our initial vision of the system. There was necessary to rethink the tool, in order to take account on the cultural variable in its development and evaluation.